Preoperative Planning and the Use of Free Available Software for Sagittal Plane Corrective Osteotomies of the Lumbar Spine in Ankylosing Spondylitis - van Royen, Barend J (Orthop Res Rev, 2020)
BACKGROUND: Ankylosing spondylitis (AS) may cause a severe rigid thoracolumbar kyphotic deformity (TLKD) that leads to considerable disturbances of posture and spinal balance. In few patients, a corrective osteotomy of the lumbar spine may be considered. Preoperative planning of a lumbar osteotomy for correction of a severe TLKD due to AS is important to correct patient’s sagittal balance and view angle. There is a need for accurate preoperative planning that can be used easily in daily practice. METHODS: The basic biomechanical and mathematical principles of preoperative planning for correction of a TLKD due to AS are described. A search was performed for free available computer programs that can be used for pre-operative planning of spinal osteotomies in AS. Finally, the use of these computer programs is illustrated and described. RESULTS: Sagittal balance is measured on a standing lateral full-length radiograph of the spine. The assessment of the pelvic parameters (PI, PT, SS) in conjunction with sagittal vertical axis (SVA) and chin-brow-to-vertical angle (CBVA) provides a comprehensive picture of the sagittal spinal alignment and compensatory mechanisms of the patient. The relation between the level of lumbar osteotomy and the amount of correction needed can be calculated with different elementary trigonometric equations. Two free available computer programs, ASKyphoplan and Surgimap, are illustrated and described that can be used for pre-operative planning of spinal osteotomies in AS. CONCLUSION: Preoperative planning of the lumbar osteotomy in AS involves assessment of the combined effect of location of the osteotomy, amount of bone resection, SVA, CBVA, and pelvic parameters. Two free available computer programs, ASKyphoplan and Surgimap, are easy to use in clinical practice to predict postoperative sagittal balance of lumbar osteotomies in patients with severe TLKD due to AS.